Fluoxetine in the environment may interfere with the neurotransmission or endocrine systems of aquatic animals - Ade Yamindago (Elsevier, 2021)
Antidepressants are extensively used to treat the symptoms of depression in humans, and the environmentally discharged drugs potentially threaten aquatic organisms. In this study, the acute toxic effects of fluoxetine (FLX) were investigated in two aquatic organisms, the freshwater polyp (Hydra magnipapillata) and Javanese medaka (Oryzias javanicus). The median lethal concentration (LC50) of FLX in H. magnipapillata was 3.678, 3.082, and 2.901 mg/L after 24, 48, and 72 h, respectively. Morphological observations of the FLX-exposed H. magnipapillata showed that 1.5 mg/L FLX induced the contraction of the tentacles and body column. The LC50 of FLX in O. javanicus was 2.046, 1.936, 1.532, and 1.237 mg/L after 24, 48, 72, and 96 h, respectively. Observation of the behavior of the FLX-exposed fish showed that FLX reduced their swimming performance at a minimum concentration of 10 µg/L. The half-maximal effective concentration (EC50) of FLX for swimming behavior in O. javanicus was 0.135, 0.108, and 0.011 mg/L after 12, 24, and 96 h, respectively. Transcriptomic analyses indicated that FLX affects various physiological and metabolic processes in both species. FLX exposure induced oxidative stress, reproductive deficiency, abnormal pattern formation, DNA damage, and neurotransmission disturbance in H. magnipapillata, whereas it adversely affected O. javanicus by inducing oxidative stress, DNA damage, endoplasmic reticulum stress, and mRNA instability. Neurotransmission-based behavioral changes and endocrine disruption were strongly suspected in the FLX-exposed fish. These results suggest that FLX affects the behavior and metabolic regulation of aquatic organisms.